Evolutionary Aspects of Acaricide-Resistance Development in Spider Mites. (2009) - Osakabe Osakabe, Masahiro (Mh.) Masahiro (Mh.); Uesugi Uesugi, Ryuji Ryuji; Goka Goka, Koichi Koichi
Abstract : Although the development of acaricide resistance in spider mites is a long-standing issue in agricultural fields, recent problems with acaricide resistance may be characterized by the development of complex- and/or multiresistance to acaricides in distinct classes. Such complexity of resistance is not likely to be a single mechanism. Pesticide resistance involves the microevolution of arthropod pests, and population genetics underlies the evolution. In this review, we address the genetic mechanisms of acaricide resistance evolution. We discuss genetic diversity and linkage of resistance genes, relationships between mite habitat and dispersal, and the effect of dispersal on population genetic structure and the dynamics of resistance genes. Finally, we attempt to present a comprehensive view of acaricide resistance evolution and suggest risks under globalization as well as possible approaches to managing acaricide resistance evolution or emergence.